Recrudescence of Toxoplasma gondii infection in chronically infected rats (Rattus norvegicus) - da Silva, Rodrigo C. [UNESP]; da Silva, Aristeu V.; Langoni, Hélio [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
The kinetics of Toxoplasma gondii infection reactivation in the brain and muscles was analyzed in this study to determine the preferred tissue by the parasite during immunosuppression. Two groups of Wistar rats (G1 and G2) were inoculated with 10(4) bradyzoites of BTU10 strain (genotype I), p.o., and other two groups (G3 and G4) were inoculated with 0.9% saline solution. G2 and G4 were immunosuppressed with dexamethasone (DXM) and hydrocortisone sodium succinate (HSS). The presence of antibodies was researched in all groups through modified agglutination test (MAT) on days 0 and 21 p.i., and brain and muscle tissues of the rats were bioassayed in mice. G2 rats died at approximately 19.2 days after drug treatment, while Cl rats survived. The reactivation was initially observed in Cl brain and G2 muscles. Thus, the initial reactivation in muscles after immunosuppression allows doctors to save precious time to control the evolution of reactivated infection, preventing brain damage to the host. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; Rattus norvegicus; Immunosuppression; Reactivation; Experimental infection; Bioassay